Is Maintenance Electroconvulsive Therapy Always an Elective Procedure?: Weighing Medical Versus Psychiatric Risk. Issue 1 (March 2018) - Rosenthal, Isobel A.; Kellner, Charles H.
Abstract : Abstract: Because of the severe nature of psychiatric illness, electroconvulsive therapy (ECT) is not always an "elective procedure." The pre-ECT medical evaluation, although important, should not be an impediment to timely ECT. We argue that an arbitrary regulation requiring new assessments every 30 days may be unduly burdensome and unnecessary. The small medical risk of treatment should be weighed against the potential psychiatric risk (including suicide) of delayed treatment.